Efektivitas Teaching Factory Dalam Meningkatkan Kompetensi Siswa Smk - Andi Saputra; Mananda Ture Siburian (Hikamatzu | Journal of Multidisciplinary, 2026)
Teaching Factory is a learning model that integrates school-based learning with real industrial production activities. This study aims to determine the effectiveness of the Teaching Factory model in improving the competencies of vocational high school (SMK) students. The research method used was a quasi-experimental design with a nonequivalent control group design. The research subjects were Grade XI students of the Mechanical Engineering expertise program at an SMK, divided into an experimental class that applied the Teaching Factory model and a control class that used conventional practical learning. Data were collected through competency tests, observation sheets, and documentation. Data analysis was carried out using descriptive statistics and inferential analysis through t-tests. The results showed that there was a significant difference in competency achievement between students who followed Teaching Factory-based learning and those who followed conventional learning. Teaching Factory learning proved effective in improving students’ technical competencies, work attitudes, and readiness for the world of work. Therefore, the Teaching Factory model can be recommended as an effective learning strategy to improve the quality of vocational education